Designing a Business Profile Video to Increase Interest in Cooperation at the Forest Smoothie Company - Chairina, Indry; Sumadewa, I Nyoman Yoga; Lazuardi, Ashar Bnyu (International Journal of Economic, Finance and Business Statistics, 2024)
Forest Smoothie faces challenges in increasing interest in cooperation with potential business partners. This research aims to design a Business Profile Video that can attract attention and increase cooperation interest in a Business-to-Business (B2B) context. The method used in this research is the pipeline method, which includes pre-production, production, and post-production stages. In the pre-production stage, needs analysis and video concept planning were conducted. The production stage involved shooting and audio recording, while the post-production stage included video editing and adding graphic elements. The results showed that the designed Business Profile Video was effective in conveying the company's message, increasing brand awareness, and attracting cooperation interest from potential business partners. Evaluation was conducted through a questionnaire that showed positive responses from respondents regarding message clarity, visual appeal, and increased interest in cooperating with Forest Smoothie.